Aqueous phase reforming (APR) of glycerol over platinum supported on Al2O3 catalyst. (January 2016) - Seretis, A.; Tsiakaras, P.
Abstract: The glycerol's APR reaction over 5% Pt/Al2 O3 catalyst for H2 production in a batch reactor is investigated in the present work. The effect of the operating parameters, such as the: i) reaction time, ii) operating temperature, iii) glycerol concentration and iv) catalyst concentration on: a) the gaseous and liquid products selectivity, b) the glycerol's conversion and c) the H2 yield is investigated. Initially, the glycerol's APR is studied at various temperature (200, 220, 240 °C) and reaction time (30, 60, 120, 240 min), using 1 wt.% or 10 wt.% glycerol solution and 0.5, 1, 2.5 g of 5% Pt/Al2 O3 catalyst weight. H2, CO, CH4 and CO2 are mainly detected in the gaseous phase and acetaldehyde, acetone, methanol, ethanol, 1-propanol, acetol, lactic acid, propylene glycol and ethylene glycol, in the liquid one. It is found that the optimum conditions were: 1 g of 5% Pt/Al2 O3, 1 wt.% glycerol solution, 240 °C and 4 h of reaction time. Under these conditions the total conversion of glycerol is found to be ∼84% (∼41% of gaseous and ∼39% of liquid products), H2 yield 14.1%, CH4 yield 3.1% and propylene glycol (the main liquid product) yield 25%. It is also found that, for 2.5 g of 5% Pt/Al2 O3, 1 wt.% glycerol solution, 240 °C and 4 h of reaction time results the total conversion of glycerol is found to be ∼68% (∼45% of gaseous and 17% of liquid products), H2 yield 16.5%, CH4 yield 7.4% and propylene glycol yield 8.1%. The increase of catalyst weight leads mostly to gaseous products. Graphical abstract: Highlights: Glycerol's APR for hydrogen production is presented. Glycerol's APH for PG production with in situ generated H2 has been performed. Reaction's time, temperature, catalyst's weights and reactants ratios are studied. Large amounts of catalyst favors only the conversion to gaseous products. The maximum H2, CH4 and PG yield was 16.5%, 7.4% and 25% respectively.